2015
DOI: 10.1109/mcom.2015.7010519
|View full text |Cite
|
Sign up to set email alerts
|

Reliable MAC design for ambient assisted living: moving the coordination to the cloud

Abstract: Ambient Assisted Living (AAL) technologies constitute a new paradigm that promises quality\ud of life enhancements in chronic-care patients and elderly people. From a communication perspective,\ud they involve heterogeneous deployments of body and ambient sensors in compex, multihop topologies.\ud Such networks can significantly benefit from the application of cooperative schemes based on network\ud coding, where random linear combinations of the original data packets are transmitted in order to\ud exploit div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…The research community has also proposed and used several wearable devices for activity monitoring systems and AAL healthcare architectures, such as [10] and [11], a few of which are briefly reviewed in this section. We refer the reader to [6] for an exhaustive survey on smart wearable technologies.…”
Section: Related Workmentioning
confidence: 99%
“…The research community has also proposed and used several wearable devices for activity monitoring systems and AAL healthcare architectures, such as [10] and [11], a few of which are briefly reviewed in this section. We refer the reader to [6] for an exhaustive survey on smart wearable technologies.…”
Section: Related Workmentioning
confidence: 99%
“…The DF-NC scheme achieves a near optimal outage probability performance while maximizing the energy efficiency of WBANs by fixing the average number of transmissions per node. In [24], the authors explored the application of NC for the cloud-assisted ambient assisted living (AAL) environments. Random linear network coding (RLNC) technology is employed to the source node to improve the efficiency of retransmission.…”
Section: Introductionmentioning
confidence: 99%
“…With the performance assessment, the authors demonstrated that their proposed protocol is superior to existing methods in the presence of channel errors for a two-hop relay network. In the following year, Kartsakli et al [7] further presented a framework for cloud-assisted ambient assisted living (AAL) applications. The proposed framework provides two planes for control operation and data operation and thus delegates network coordination tasks to the cloud.…”
Section: Introductionmentioning
confidence: 99%